PENERAPAN DISKRESI OLEH SATUAN POLISI LALU LINTAS DI WILAYAH HUKUM KEPOLISIAN RESOR PAYAKUMBUH - Wistya Tri Vani; Erdianto '; Rahmat Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Discretion is the authority of the police to make a decision or choose different actionsin resolving issues of law violations or criminal cases are handled. Discretion became one ofthe alternatives in criminal cases penyelesasian traffic. The increasing number of residents inthe District Fifty Cities affect the number of vehicles are also increasing proportional to theincreasing traffic violations that occurred, the crime of traffic recorded at the PolicePayakumbuh in 2015 to handle 132 criminal cases traffic and 88 case settled throughdiscretion. Implementation of discretion in a professional manner and in accordance with thecode of police ethics becomes a necessity for police to avoid abuse of office. Discretionrequire an adequate level of intelligence in making decisions. In this case the humanresources (HR) law enforcement plays an important role of the contents of law products.Keywords : Implementation-discretion-Traffic Police Unit